Problems of Multinacional Literature course - P. Užkalnis (Literatūra (Vilnius))
The author of the paper reviews the history of the Soviet Union national literature of a 40-year period, its various construction methods and variants, and the projects of "The Program," upholding the historical course construction principle. Synthesizing the USSR national literature process, the author marks off the typological parallels of the multinational literary process, singling out the evolution of the concept of the human being as the most important. The author refers to the tenets of the classics of Marxism that "history is not something indefinite" but is created by the real, live man, pursuing his aim, creating the surroundings in which he himself is moulded.